2018
DOI: 10.1177/2158244018784643
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Effect of Dynamic Assessment on the EFL Learners’ Process Writing Development

Abstract: The present study was undertaken to explore the practicality and the effect of dynamic assessment on L2 writing ability of Iranian English as a foreign language (EFL) learners. To this end, 17 EFL learners divided into two groups, participated in this article. Then, dynamic assessment procedure was done in three steps, topic-choice, idea-generation, and macrorevising. All these steps ran with the mediation of the teacher and also the learners together. The results of the study indicated that dynamic assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It gives the learners a push to exhibit their talent with an expectation to be appreciated and applauded, as is the human tendency. Rashidi and Najed (2018) and Hidri (2019) concluded that Dynamic Assessment had a positive impact, especially on the syntactic forms which are considered as a major challenge by the EFL learners due to remarkable differences in the syntactic pattern between Arabic and English. The learners at Prince Sattam University and Qassim University showed improvements in their writings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives the learners a push to exhibit their talent with an expectation to be appreciated and applauded, as is the human tendency. Rashidi and Najed (2018) and Hidri (2019) concluded that Dynamic Assessment had a positive impact, especially on the syntactic forms which are considered as a major challenge by the EFL learners due to remarkable differences in the syntactic pattern between Arabic and English. The learners at Prince Sattam University and Qassim University showed improvements in their writings.…”
Section: Discussionmentioning
confidence: 99%
“…The result testifies the third study question, for the teacher mediates as interventionist and interactionist to improve learning by providing sequential prompts. Rashidi and Najed (2018), Adeline (2012), Dimitrios and Athanasia (2019), recommend this tendency. As per the results, 59.1% of respondents agreed with devoting instructional time during classes to fill learning gaps, and 56.8% of respondents preferred giving all the instructions at a time for a specific task.…”
Section: Interview Protocolmentioning
confidence: 99%
“…Since the positive effect of metacognitive awareness on language learners' achievement is confirmed in many studies in the literature (Boekaerts, Pintrich, & Zeidner, 2000;Bolitho et al, 2003;Eilam & Aharon, 2003;Salehi & Farzad ,2003;Mokhtari & Reichard, 2002;Palmer & Goetz, 1988;Victori & Lockhart, 1995;Zimmerman & Schunk, 2001;Purpura, 1997Purpura, , 1998Ajideh & Nourdad ,2012;Hessamy & Ghaderi, 2014;Levi ,2016;Bahadori Nejad ;,Minakova, 2020, investigating the potential effect of DA on metacognitive awareness of language learners is of significant importance which has not been explored adequately in the literature of English language learning in general and Iranian EFL settings in particular.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Studies conducted to determine factors resulting to low-performance level among learners have revealed that there is no correlation between their performance, learning potential, and social backgrounds. According to these studies, many learners fail in static tests due to a lack of opportunities for learning experiences, cultural differences, special learning difficulties, or traumatic life experiences (Rashidi et al, 2018). Therefore, dynamic assessment has been recommended to be used in psychoanalysis and counseling fields (Cornfield, 2001;Falik, 2000;Haywood & Lidz, 2007).…”
Section: What Is Dynamic Assessmentmentioning
confidence: 99%
“…Moreover, diversified research on dynamic assessment in second language context focuses on the classroom and the interaction between learner and mediator, and finally how this interaction functions to understand and improve learner's proficiency (Lantolf & Poehner, 2011). As it has been stated by Rashidi and Nejad (2018) in their study that investigates the effects of dynamic assessment on the EFL learners writing development, that the ultimate goals of dynamic assessment are for promoting development and providing learners' motivation. They have found in their study that learners made remarkable improvement as a result of the mediations that have been made based on the most salient concept of ZPD, developed by Vygotsky.…”
Section: The Effects Of Dynamic Assessment On Language Learnersmentioning
confidence: 99%